Periodismo y literatura en Costa Rica (1833-1950) - Vega Jiménez, Patricia (2016)
This article analyzes the relationship between the development of journalism and literature, specifically the participation of Costa Rican writers in the press and the role played by the press in the publicity of literature. The journey to fulfill these objectives begins in 1833 and ends in 1950; this long period helps us identify the changes and continuities over time and therefore establish a comparative analysis.